Encouraging Use of Subordination in Children's Narratives: A Classroom-Based Priming Study. Issue 4 (1st October 2016) - Hesketh, Anne; Serratrice, Ludovica; Ashworth, Rachel
ABSTRACT: This study investigated the long-term effect of classroom-based input manipulation on children's use of subordination in a story re-telling task; it also explored the role of receptive vocabulary skills and expressive grammatical abilities in predicting the likelihood of priming. During a two-week priming phase, 47 monolingual English-speaking five-year-olds heard 10 stories, one a day, that either contained a high proportion of subordinate clauses (subordination condition) or a high proportion of coordinate clauses (coordination condition). Post-intervention, there was a significant group difference in likelihood of subordinate use which persisted ten weeks after the priming. Neither expressive grammatical nor receptive vocabulary skills were positively correlated with the likelihood of subordinate use. These findings show that input manipulation can have a facilitative effect on the use of complex syntax over several weeks in a realistic communicative task.